2022
DOI: 10.3389/fmed.2022.799736
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Outbreak on the Gynecological Outpatients HPV Infection Rate in Wuhan, China: A Retrospective Observational Study

Abstract: BackgroundThe recent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak has caused millions of deaths and greatly influenced the timely diagnosis and treatment of other diseases. Throughout the pandemic, there was a dramatic reduction in the prevalence of several sexually transmitted infections. However, the impact of the ongoing pandemic on human papillomavirus (HPV) infection rates has not been investigated thus far.Materials and MethodsWe retrospectively collected data regarding HPV and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Considering that HPV infections may increase rapidly after the pandemic. 28 We recommend the immediate implementation of effective HPV, cervical cancer screening, and HPV vaccine programs to reduce the spread of HPV infections. The global confrontation with COVID-19 has not only diverted current healthcare resources to deal with the infection but has also resulted in increased resources in the areas of testing and screening, as well as educating most of the global public of the benefits of vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that HPV infections may increase rapidly after the pandemic. 28 We recommend the immediate implementation of effective HPV, cervical cancer screening, and HPV vaccine programs to reduce the spread of HPV infections. The global confrontation with COVID-19 has not only diverted current healthcare resources to deal with the infection but has also resulted in increased resources in the areas of testing and screening, as well as educating most of the global public of the benefits of vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54] Thus, acknowledging the role of HPV infection in males as a conduit for HPV transmission to females could significantly influence the adoption of preventive measures for cervical health. The overall incidence of HPV infection appeared to have decreased during the pandemic 55 ; however, our study revealed an unexpected trend in which male HPV infection rates remained unaffected by isolation and containment measures. Specifically, our data indicated that the prevalence of HPV infection among males increased from 23.93% in the prepandemic to 25.86% during the pandemic, with both HR-HPV and LR-HPV infections showing the upward trend (HR-HPV: 21.92% vs. 23.64%; LR-HPV: 3.06% vs.…”
Section: Discussionmentioning
confidence: 49%
“…Additionally, nonpharmaceutical interventions for HPV transmission likely led to reduced access to health services, resulting in an elevated risk of undiagnosed HPV [ 31 ]. However, as the pandemic subsides and social activities gradually resume, coupled with reduced vaccination rates during this period [ 32 ], there is a potential surge in HPV infection rates [ 33 ]. Therefore, it is crucial to promptly enhance HPV screening and vaccination strategies to mitigate the potential surge in HPV dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…These genotypes can be categorized into high-risk (HR) and low-risk (LR) types based on their carcinogenic potential. Epidemiological studies and mechanistic evidence have revealed that HPV16, 18,31,33,35,39,45,51,52,56,58, and 59 are carcinogenic, while HPV68 is considered potentially carcinogenic [6]. Currently, HPV vaccination and screening are the primary strategies for preventing cervical cancer.…”
Section: Introductionmentioning
confidence: 99%